RANCANG BANGUN PROTOTIPE KENDALI OTOMATIS KANOPI GESER PADA JEMURAN BERBASIS TELEGRAM - amelia, putri (Jurnal Sains dan Teknologi Tadulako, 2025)
Technological developments in the era of globalization, especially the Internet of Things (IoT), allow devices to connect and interact with each other through the internet network in real-time. This technology supports the management of electronic devices, household appliances, and other objects through the ESP32 microcontroller that can collect and transmit data. This research designed an automatic sliding canopy system for the dressing room that can operate independently using a rain and light sensor based on the NodeMCU ESP32 microcontroller. The system is designed to automatically close the canopy when the rain sensor detects the presence of rainwater and the light sensor detects dark conditions, so the clothesline is protected from rain. In addition, this system is equipped with remote monitoring and control features through the Telegram application using Bots.